Barriers to career advancement of black professionals into managerial positions in a steel manufacturing company in South Africa - Makena, Andrew Senakangwedi (My University, 2015)
ABSTRACT The aim of this study was to identify barriers to the career advancement of Black professionals into managerial positions. The need for the study stems from the current statistics reported in the 2012/2013 Commission for Employment Equity (CEE) Report, showing that there is still disparity in the representation of Black professionals at management level. The study was limited to the manufacturing industry. A qualitative study was conducted at a South African steel manufacturing company which is not meeting the Employment Equity (EE) target as far as such representation is concerned. One-on-one interviews were conducted on 12 Black professionals in the professionally qualified category as defined by the CEE reporting i.e. a level below senior management. The analysis was done on the basis of the participant’s background, exposure in the steel manufacturing environment, age and job level. The findings indicate that EE policies are in place but the translation of policies into practical means by Leadership is still a challenge due to the prevalent lack of congruence between EE policies and the existing organisational culture. As such the environment is not conducive to advancement of Blacks into managerial positions. The study concludes that barriers to career advancement of Black professionals into managerial positions will still be active and in force unless there is a drastic culture change in support of transformation through implementation of the recommendations made. There is a need for further research and this is proposed in order to gain an understanding and to resolve the challenges currently faced.
MBA Thesis 2015
Keywords: Executives, Black,Professional employees -- South Africa,Blacks -- Employment ,Affirmative action programs